Prognostic value of LncRNA PSMA3-AS1 in prostate cancer and its potential regulatory mechanism - Muyang Cao; Jin Li; Jianbin Zhang; Wenlong Lu (Hereditas)
Abstract Objective Prostate adenocarcinoma (PRAD) is asymptomatic in the early stages and most patients are diagnosed at an advanced stage, which leads to a poor prognosis. Therefore, an effective prognostic marker is required to improve PRAD prognosis. Methods A total of 128 patients with PRAD were included in the study. PSMA3-AS1 and miR-29a-3p expression in tissues was detected using RT-qPCR. CCK-8 and Transwell assays were then used to evaluate the proliferative, migratory, and invasive capacities of prostate cancer cell lines. A DLR assay confirmed the binding relationship between PSMA3-AS1 and miR-29a-3p. The five-year prognosis of PRAD patients was analyzed using a Kaplan–Meier plotter curve. Results PSMA3-AS1 was highly expressed in PRAD tissues, and patients with high expression had poor 5-year survival. In contrast, miR-29a-3p was poorly expressed in PRAD tissues. PSMA3-AS1 bound to miR-29a-3p in a targeted manner and the levels showed a negative correlation. Knocking down PSMA3-AS1 could increase the level of miR-29a-3p and slow the proliferation of PRAD cell lines, as well as inhibiting their migration and invasion ability. Conclusion A high level of PSMA3-AS1 was strongly linked to a poor prognosis for patients and is expected to serve as a prognostic marker for PRAD. Furthermore, PSMA3-AS1 knockdown increased the level of miR-29a-3p and reduced the physiological activity of cancer cells. Therefore, regulating the expression of the PSMA3-AS1/miR-29a-3p axis could influence PRAD development.